A Computational Tool for Recoloring Based on User Emotions - Son, Jungah; Peljhan, Marko; Legrady, George; Sra, Misha (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2023)
This work describes a system to recolor a user’s painting based on the perceived emotional state of the viewer. An automatic palette selection algorithm is used to generate color palettes for a set of emotions. A user can create a painting using one of the generated palettes. To notify the end of the painting, the user clicks on the DONE button. Once the button is pressed, the colors of the user's painting change as the facial expression of the user changes. Facial emotion recognition is used in this process to classify the emotional status of the user’s face.